PARASITOSES INTESTINAIS: GIARDIA LAMBLIA - Padilha, Doriana Aparecida de Campos; Xavier, Jovanildes; Tavares, Daiane; Campos, Ingrid Greiziely De Souza; Lemes, Artiana; Santos, Fábio Alexandre Leal dos (Seminários de Biomedicina do Univag, 2017)
>>> ver PDF